Penanganan Teror Bom Thamrin Ditinjau Berdasarkan Skep Kapolri Nomor: 172 Tahun 2014 tentang Penanganan Tempat Kejadian Perkara (PTKP) Bom - Tabrani, Dedy (Jurnal Keamanan Nasional, 2016)
ISIS phenomena after Al-Qaeda have given new hope and spirit of Islamic radicalism groups in Indonesia. One of terrorism action by ISIS members was Thamrin bombing terror on January 14, 2016 with pattern and modus of bombings and shootings. Indonesian National Police as a leading sector in handling terrorism has formulated rules regarding terrorism handling, such as the Decree of the Indonesian National Police Chief (Perkap) No. 172, 2014 on the Handling of the Crime Scene (PTKP) of bomb. This decree becomes the base of police on handling terror scene. Therefore, this research can reveal how far the handling of Thamrin terror bombing based on Skep No. 173, 2014.